Nitrogen-fixing microbes gain genes in diverse types of living environments - Hong-Wei Pi; Chun-Ping Yu; Ya-Fei Chen; Bing-Syuan Wu; Li-Yin Peng; Wen-Hsiung Li (Proceedings of the National Academy of Sciences, 2025)
Biological nitrogen fixation (BNF), which is catalyzed by a large nitrogenase enzyme complex, has evolved in both bacteria and archaea. Indeed, nitrogen-fixing species are found in diverse living environments, and BNF has evolved even in aerobic bacteria, although the function of nitrogenase is inhibited by oxygen. BNF is, however, highly energy-costing, requiring 16 ATPs in a single nitrogen fixation reaction. To explain this paradox, we hypothesized that nitrogen-fixing species gain not only nitrogen-fixing ( nif ) genes but also non- nif genes to facilitate nitrogen fixation. We examined over 3500 nitrogen-fixing genomes and found that they have gained genes directly or indirectly related to BNF in diverse types of living environments, so that nitrogen-fixing species tend to have larger genomes than their non-nitrogen-fixing relatives. Interestingly, the non- nif genes gained tend to be located near nif -gene clusters, probably to achieve proximity effects such as coordinated gene regulation. For example, the most frequent among the genes gained are ABC transporter genes, which facilitate the absorption and physiological metabolism of carbon (e.g., sugars), nitrogen (e.g., amino acids), and trace elements (e.g., molybdenum), and many ABC transporter genes lie close to nif -gene clusters. From our findings, we propose the following scenario: BNF evolved in many archaea and bacteria because BNF is advantageous to its hosts, although it incurs a high energy cost. Then, gaining genes to facilitate BNF compensates the cost of BNF, facilitating the spread of nitrogen fixers to all living habitats. This expansion benefits the biosphere, as nitrogen is essential for all organisms.